For a Reinterpretation of the Fishermen’s Altar of Pedo/Pedona (CIL V 7850 = ILS 3827) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2024)
In this article, we propose a new interpretation of the text of a dedication to Neptunus from the Alpine area of Roman Liguria (from Pedo/Pedona - Regio IX). Th e elements Carb(- - -), Ebelin(- - -), and Barg(- - -), previously interpreted as toponyms of uncertain location, along with Peda, considered the original form of the place name Pedo/Pedona, would instead refer to individual offerings from a collegium for the construction of a composite wooden statue intended for the worship of the river deity.
Keywords: Latin epigraphy; piscatores; Regio IX; Neptunus; wooden statue